2021
DOI: 10.48550/arxiv.2108.09560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution of values of Gaussian hypergeometric functions

Abstract: In the 1980's, Greene defined hypergeometric functions over finite fields using Jacobi sums. The framework of his theory establishes that these functions possess many properties that are analogous to those of the classical hypergeometric series studied by Gauss and Kummer. These functions have played important roles in the study of Apéry-style supercongruences, the Eichler-Selberg trace formula, Galois representations, and zeta-functions of arithmetic varieties. We study the value distribution (over large fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 61 publications
(69 reference statements)
0
10
0
Order By: Relevance
“…In this section, we show how to use the inductive representation introduced in §3 to evaluate first and second moments of Gaussian hypergeometric functions over F q . In [13], explicit representations of moments of the hypergeometric functions 2 F 1 and 3 F 2 were given. Namely, the sums of the form…”
Section: Evaluation Of Moments Of Gaussian Hypergeometric Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we show how to use the inductive representation introduced in §3 to evaluate first and second moments of Gaussian hypergeometric functions over F q . In [13], explicit representations of moments of the hypergeometric functions 2 F 1 and 3 F 2 were given. Namely, the sums of the form…”
Section: Evaluation Of Moments Of Gaussian Hypergeometric Functionsmentioning
confidence: 99%
“…Remark 1. Proposition 4.2 was proved for n = 1 and q ≡ 3 (mod 4) in [13,Proposition 2.11 (3)]. When q ≡ 1 (mod 4), comparing Proposition 4.2 to [13, Proposition 2.11 (4)] implies the existence of a rational number D(q) ∈ [−6, 6] such that gcd(s,q)=1 s≡q+1 (mod 8)…”
Section: Traces Of Elliptic Curves and Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important fact about these functions is that they satisfy many analogous hypergeometric type identities. Recently Ono, Saad and the second author [21] initiated a study of value distributions of certain families of these functions over random large finite fields F q . More precisely, they investigated the distributions of the normalized values of the following two Gaussian hypergeometric functions over F q that are defined by…”
Section: Introductionmentioning
confidence: 99%
“…is the normalized Jacobi sum. Ono et al [21] showed that for the 2 F 1 (λ) q function the limiting distribution is semicircular whereas for the 3 F 2 (λ) q function the distribution is Batman. In this paper our goal is to study similar questions for p-adic hypergeometric functions over random large finite fields.…”
Section: Introductionmentioning
confidence: 99%